2010
DOI: 10.1002/jctb.2434
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of acrolein by gas‐phase dehydration of glycerol over silica supported Bronsted acidic ionic liquid catalysts

Abstract: BACKGROUND: Glycerol has become readily available as a byproduct from the biodiesel industry. High functionality and relatively low price make it a potential building block to produce value-added derivatives such as acrolein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Gas-phase dehydration of glycerol to produce acrolein was studied using a series of silica supported Brønsted acidic IL catalysts. 308 Acrolein is a key intermediate for the synthesis of acrylic esters, super absorbers, polymers, and detergents. All catalysts in this study were found to be active in the dehydration of glycerol.…”
Section: Supported Ils Based Catalystsmentioning
confidence: 99%
“…Gas-phase dehydration of glycerol to produce acrolein was studied using a series of silica supported Brønsted acidic IL catalysts. 308 Acrolein is a key intermediate for the synthesis of acrylic esters, super absorbers, polymers, and detergents. All catalysts in this study were found to be active in the dehydration of glycerol.…”
Section: Supported Ils Based Catalystsmentioning
confidence: 99%
“…Glycerol is an abundant renewable resource for the production of biomaterials as well as a source for a great variety of chemical intermediates . Glycerol is also an efficient platform for the synthesis of oxygenated compounds such as polyglycerols and glycerol ethers by means of the etherification process …”
Section: Introductionmentioning
confidence: 99%
“…Several catalyst systems have been investigated, for example, zeolites [14,15], heteropolyacids [16,17], mixed oxides [18], WO 3 /TiO 2 [19], WO 3 /ZrO 2 [20], unsupported [21] and supported Nb 2 O 5 [22,23], Ta 2 O 5 [24], bifunctional MO x -Al 2 O 3 -PO 4 catalysts [25,26], rare earth pyrophosphates [27], zirconium phosphate [28] and other classes such as silica-supported ionic liquids [29].…”
Section: Accepted Manuscriptmentioning
confidence: 99%